Health Care Reform's Proposed End-of-Life Provisions - Brandy C. Hill; Nick Lebredo; Christopher R. Shafer (University of North Florida, 2010)
End-of-life planning promotes patient autonomy by allowing individual patients to inform and direct care givers and healthcare proxies on their desired level of end-of-life care, where the patient prefers to pass away (whether at home or in a hospital setting), and the methods and levels of pain management that the patient deems desirable. Given that, it is counter-intuitive that a significant majority of American's fail to execute, or fail to properly execute, advance directives. Theauthor'seffortsfocusonwhatcanbedonetoimprove,generally,end-of-lifecare. Tothatend,theauthorsconclude that improvements in end-of-life care must be achieved at three levels: the individual level, the healthcare provider level, andatthegovernmentlevel. Ontheindividuallevel,patientsmustassumegreateraccountabilityfortheirownend-of-life care. Thatentailsmakingone'swishesforend-of-lifecareknowntofamilymembersandhealthcareproviders. Onthe healthcare provider level, improved patient communication and improved delivery of palliative-oriented care are first order initiatives. Finally, the government can play a significant role in improving end-of-life care by collecting better healthcare utilization and cost data on end-of-life experiences, expanding benefits for palliative care services, and promoting the use of advance directives through legislative efforts that include patient education measures.